KACA: Educational Tutorial Video-Based Games to Stimulate Early Childhood Language Skills - Winardi, Diva Winding Seciola Syakhinna; Widiana, I Wayan (Jurnal Pendidikan Anak Usia Dini Undiksha, 2024)
Several findings regarding children's difficulties in reading show that out of a total of 11 children in the class, 8 of them still experience difficulties in initial reading. In addition, researchers also noted that the main reason for these difficulties was due to the slow process of letter recognition in these children. This research aims to develop the "Reading Calendar" (KACA) media, to stimulate children's language skills. This research uses a development approach with the ADDIE model which consists of analysis, design, development, implementation and evaluation. The object of this development research is the learning media educational game tool "Reading Calendar" (KACA) based on educational video tutorials, with a focus on content validity, teacher response, and product effectiveness. The research subjects consisted of ten children from group B, with the children's language abilities as the research object. Data collection methods use observation, rating scales, and questionnaires. Data analysis involves testing validity using the Gregory formula and practicality by teachers using the Aiken formula. The research results show that this learning media is effective in increasing children's interest in learning and providing significant support for teacher performance. This shows that the new reading calendar media based on educational video tutorials is a viable, practical and effective choice in improving the language skills of children in group B. This research has implications for increasing interest and involvement of media in the learning process, so that it can create a better learning experience interesting.